PROTECTION OF THE RIGHT TO OWNERSHIP IN MACEDONIAN PROPERTY LAW - Przheska, Tina; Živkovska, Rodna (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2023)
The paper analyses the legal remedies for the protection of the right of ownership in Macedonian property law and in comparative law. This research focuses on the protection of ownership in the Macedonian property law system, as guaranteed by the provisions of the basic Ownership and Other Property Rights Act. This Act regulates different types of petitory actions (lawsuits) for the protection against infringement or interference with the ownership right whose scope and effectiveness will be analyzed in this paper. The analysis will extend to special laws regulating some form of protection of the ownership right. The paper also includes a comparative analysis of the legal mechanisms for protecting the right of ownership in the legal system of EU member states and other European countries, pinpointing the similarities and differences in the legal approach to protecting the right of ownership between countries. Considering that the right of ownership is protected by Protocol 1 of the European Convention on Human Rights, the paper will also address the European Court of Human Rights approach to protecting the ownership right under the Convention.